Acidity‐Triggered Transformable Polypeptide Self‐Assembly to Initiate Tumor‐Specific Biomineralization (Adv. Mater. 15/2023). Issue 15 (13th April 2023) - Liu, Yang; Jiang, Zhongyu; Tong, Shizheng; Sun, Yifu; Zhang, Yu; Zhang, Jiayuan; Zhao, Duoyi; Su, Yuanzhen; Ding, Jianxun; Chen, Xuesi
Abstract : Therapeutic Transformable Polypeptides In article number 2203291, Jianxun Ding, Xuesi Chen, and co‐workers report a therapeutic transformable polypeptide nanoparticle that initiates selective biomineralization for effective blockade therapy of osteosarcoma after activation by the acidic tumor microenvironment, through triggering continuous ion deposition to construct a mineralized barrier around the tumor and alleviate bone dissolution. The strategy indicates significant potential for clinical osteosarcoma therapy.